HUBUNGAN PERTUMBUHAN PENDUDUK DENGAN TUJUAN PEMBANGUNAN BERKELANJUTAN DI SUMATERA - Ery Jayanti (Syiah Kuala University, 2017)
Sustainable development is a new paradigm in the economic development literature and an important issue, that is, development of welfare and environmental approaches. Because without regard to sustainable development, it will lose the potential of agreen economy in the GRDP. Hence Population becomes an issue that is not simple for sustainable development, regarding quantity and quality, this becomes necessary to understand and find the positive and negative impact of population growthThe purpose of this study was to analyze the interdependence relationship between population growth and sustainable development using panel data in five provinces in Sumatra for the period 2005-2016, with the Fixed Effect Model (FEM) approach,The results showed that there issimultaneously a significant influence on population growth and all variables of sustainable development, partially some variables are not relevant. The relationship of Population growth and birth rate indicators has no effect on food security, population displacement variables and birth rates have no significant impact on the exploitation of natural resources, on signs of petroleum lifting.The results of this study are expected to be considered in the decision making of the Indonesian government, especially Sumatra, to establish a clear policy on environmental issues concerning forests, food security, and energy security. It is expected that the Government makes a serious breakthrough on the quantity and quality of life of the population so that the people do not become an obstacle to sustainable development but become the trigger of development in the long term.